Effects of Different Components of Buyang Huanwu Tang on the PPARγ/LXRα/ABCA1 Pathway in Hypercholesterolemia Mouse Model - Shuaihu Yang; Yukun Zhang; Xinxin Liu; Xingtong Chen; Yuxue Ma; Shijian Fang; Ruihong Yang; Jinbiao Yang; Yunyue Zhou; Xiao He; Pengcheng Li; Hongbin Xiao; et al. (International Journal of Genomics, 2025)
The aim of this study is to compare the effects of different components of Buyang Huanwu Tang (BYHWT) on the peroxisome proliferator-activated receptor γ (PPARγ)/liver X receptor α (LXRα)/ATP-binding cassette transporter A1 (ABCA1) pathway and its lipid-lowering effects. This study shows that the BYHWT alcohol precipitation and 75% alcohol components can significantly reduce the serum levels of triglycerides (TGs), low-density lipoprotein (LDL), cholesterol (CHO), and hepatic function damage indicators such as glutamic oxaloacetic transaminase (AST) and glutamic pyruvic transaminase (ALT) in hypercholesterolemia mouse model. After treatment, the presence of lipid droplets in liver cells was reduced, and the destruction of adipocytes was improved. The Western blot (WB) results showed that alcohol precipitation and 75% alcohol components can upregulate PPARγ, ABCA1, and LXRα. The expression of these components indicates that PPARγ upregulation can activate LXRα, thus regulating the expression of ABCA1, mediating CHO efflux, promoting reverse cholesterol transport (RCT), and regulating the downstream gene CYP7A1 to participate in bile acid synthesis and metabolism. In summary, the experimental results indicate that the BYHWT alcohol precipitation, 50% alcohol, and 75% alcohol components can modulate the PPARγ/LXRα/ABCA1 pathway in hypercholesterolemia mouse model to promote CHO metabolism.